SISTEM KONTROL KECEPATAN MOTOR DC MENGGUNAKAN PID PADA ROBOT PEMBAWA MAKANAN - Muhammad Ihsan Zuhdi; Gavin Allufi Yanno; Indra Dwisaputra; Aan Febriansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
DC motors are the most commonly used actuators in both small and large scale industries. Dc motor speed often decreases due to several factors so that the speed becomes unstable, one of the factors of the speed of the DC motor is unstable is the presence of load. In this study, a PID control system was created to regulate the speed of the DC motor. The output of the PID control is PWM which later the PWM value will go to the motor driver. The process will continue to repeat until the output value is close to or equal to the setpoint value that has been determined. Determination of variable values Kp, Ki and Kd using the method of trial and error. These values that later affect the PID control process. Using PID controls, the dc motor can rotate more stablely. If the dc motor's speed is stable, it can reduce vibrations in the food delivery robot and reduce the impact at the start of the DC motor at the beginning. The result and conclusion of this study is that each RPM value we want has a different Value kp, Ki and Kd, for example for the value of RPM 200 then the value of Kp = 0.5 Ki = 0.75 and Kd = 0.03, while for the value of RPM 400 then the value of Kp = 0.3 Ki = 0.88 and Kd 0.002.